Strategi komunikasi Badan Pusat Statistik (BPS) Indonesia dalam mewujudkan “satu data perkebunan” - Pradhana, Chandra; Sumartias, Suwandi; Rahmat, Agus (Universitas Negeri Malang, 2025)
The communication strategy of Indonesia’s Central Bureau of Statistics (BPS) in realizing the “one plantation data” initiative This study aims to understand how the Communication Strategies of the Indonesian Central Statistics Agency (BPS) innovate to develop a data collection system for large companies under BPS’s responsibility. The informants in this research are Civil Servants from the Directorate of Statistics for Food Crops, Horticulture, and Plantations and representatives from plantation companies. The research uses a qualitative approach with a descriptive method. Theories applied include the Interpersonal Communication Theory by Joseph A. Devito and the Diffusion of Innovations Theory by Everett M. Rogers. The findings of this study indicate that the interpersonal communication strategies implemented, including openness, empathy, supportive attitudes, positive feelings, and equality, are vital in developing an innovative data collection system for large companies. The centralized diffusion communication model implies that the dissemination of innovation is carried out linearly from BPS to the relevant stakeholders through team coordination, involvement of plantation companies, the development of the Sedia Data Perkebunan Online system (SEDAPP Online), and training for operators from each company. Through SEDAPP Online, BPS can engage stakeholders actively in realizing